STEM Applications in Turkish Science High Schools - Mustafa Hilmi Colakoglu (Journal of Education in Science, Environment and Health)
The idea of establishing Science High Schools in Turkey was discussed in a multilateral project at the beginning of 1963. The Ministry of National Education (MoNE), Ford Foundation, Middle East Technical University (METU), Ankara University, and International Development Agency (AID) participated in this project to establish these schools. In Ankara, Science High School project was a US funded and technically supported project, carried out jointly by the Florida State University, METU, and Ankara University. Science High Schools’ organizational goals were: (1) to improve students’ ability and increase their intelligence in science (2) to increase the number of qualified personnel in higher education and industry, and (3) to develop more laboratories by increasing students’ scientific knowledge in order to be the center of research and development. MoNE created the "Science High School Project Advisory Board" with six members from Ankara University and four members from METU to contribute to the scientific and curriculum aspects of the project. The Advisory Board selected 30 teachers from Mathematics, Chemistry, Physics and Biology disciplines by written and oral exams from the existing high schools of MoNE from all over the Turkey. Selected science teachers received special training for the development regarding the assessments of subjects and provided with opportunities to study on the curriculum at some universities in the United States (U.S.). To train teachers in Turkey, a modern building was constructed at METU campus and the education at Ankara Science High School started in 1964. After the success of the Ankara Science High School, the MoNE started the Science High School Projects in Istanbul and Izmir. Today, there are 238 Science High Schools serving as public schools and the same amount of schools serving as private schools. In the U. S., the training of 100K STEM teachers started in 2012. In this article, Science High Schools’ development and their innovation activities, the STEM projects and the vision for increasing the STEM education in Turkey and other developed countries were discussed.